Chorionic gonadotropin and uterine dialogue in the primate - Strakova Zuzana; Srisuparp Santha; Cameo Paula; Fazleabas Asgerally T (BMC, 2004)
Abstract Implantation is a complex spatio-temporal interaction between the growing embryo and the mother, where both players need to be highly synchronized to be able to establish an effective communication to ensure a successful pregnancy. Using our in vivo baboon model we have shown that Chorionic Gonadotropin (CG), as the major trophoblast derived signal, not only rescues the corpus luteum but also modulates the uterine environment in preparation for implantation. This response is characterized by an alteration in both the morphological and biochemical activity in the three major cell types: luminal and glandular epithelium and stromal fibroblasts. Furthermore, CG and factors from the ovary have a synergistic effect on the receptive endometrium. Novel local effects of CG which influence the immune system to permit the survival of the fetal allograft and prevent endometrial cell death are also discussed in this review. An alternate extracellular signal-regulated kinase (ERK) activation pathway observed in epithelial endometrial cells and the possibility of differential expression of the CG/LH-R isoforms during gestation, open many questions regarding the mechanism of action of CG and its signal transduction pathway within the primate endometrium.